Comparison of the Effects of Anesthesia Methods on Dynamic Thiol/Disulfide Homeostasis in Patients with Chronic Obstructive Pulmonary Disease Under Surgical Stress - Çelik, Fatma; Dagli, Recai; İlanbey, Bilal (My University, 2024)
Purpose: Chronic Obstructive Pulmonary Disease (COPD) is linked to increased oxidative stress. Changing oxidative stress status due to anesthesia applications may affect surgical stress and the incidence of postoperative complications. This study aims to contrast the impacts of general anesthesia (GA) and spinal anesthesia (SA) on the dynamic thiol-disulfide homeostasis among patients with COPD who are undergoing inguinal hernia surgery. Materials and Methods: According to the 2017 Global Strategy Report for the Diagnosis, Management and Prevention of COPD, patients with airflow obstruction (50%?FEV1<79%) and FEV1/FVC<0.7% were evaluated. A total of 52 COPD patients, group GA (n=26) and group SA (n=26), scheduled for inguinal hernia surgery were included in this observational study. Blood samples were collected preoperatively and at 24 hours postoperatively. Parameters of thiol/disulfide balance were analyzed. Results: In both group GA and group SA, a decrease in total thiol, native thiol and disulfide values was observed after anesthesia compared to pre-anesthesia. However, only in group SA, the decrease in total thiol (p<0.01) and native thiol (p=0.012) values after anesthesia was statistically significant. The change in other variables was not statistically significant. There was no significant difference between group GA and group SA in the thiol/disulfite variables before and after anesthesia. Conclusion: General and spinal anesthesia methods demonstrated a similar response on dynamic thiol/disulfide homeostasis in COPD patients under surgical stress.
Keywords: Oxidative stress; COPD; disulfide; thiol; spinal anesthesia